The genetic basis and adult reproductive consequences of developmental thermal plasticity. - Rodrigues, L.R.; Zwoinska, M.K.; Wiberg, R.A.W.; Snook, R.R. (Journal of Animal Ecology, 2022)
Increasing temperature and thermal variability generate profound selection on populations. Given the fast rate of environmental change, understanding the role of plasticity and genetic adaptation in response to increasing temperatures is critical. This may be especially true for thermal effects on reproductive traits in which thermal fertility limits at high temperatures may be lower than for survival traits. Consequences of changing environments during development on adult phenotypes may be particularly problematic for core traits such as reproduction that begin early in development. Here we examine the consequences of developmental thermal plasticity on subsequent adult reproductive traits and its genetic basis. We used a panel of Drosophila melanogaster (the Drosophila Genetic Reference Panel; DGRP) in which male fertility performance was previously defined as either showing relatively little (status = 'high'-performing lines) or substantial ('low'-performing lines) decline when exposed to increasing developmental temperatures. We used a thermal reaction norm approach to quantify variation in the consequences of developmental thermal plasticity on multiple adult reproductive traits, including sex-specific responses, and to identify candidate genes underlying such variation. Developmental thermal stress impacted the means and thermal reaction norms of all reproductive traits except offspring sex ratio. Mating success declined as temperature increased with no difference between high and low lines, whereas increasing temperature resulted in declines for both male and female fertility and productivity but depended on line status. Fertility and offspring number were positively correlated within and between the sexes across lines, but males were more affected than females. We identified 933 SNPs with significant evolved genetic differentiation between high and low lines. In all, 54 of these lie within genomic windows of overall high differentiation, have significant effects of genotype on the male thermal reaction norm for productivity and are associated with 16 genes enriched for phenotypes affecting reproduction, stress responses and autophagy in Drosophila and other organisms. Our results illustrate considerable plasticity in male thermal limits on several reproductive traits following development at high temperature, and we identify differentiated loci with relevant phenotypic effects that may contribute to this population variation. While our work is on a single population, phenotypic results align with an increasing number of studies demonstrating the potential for stronger selection of thermal stress on reproductive traits, particularly in males. Such large fitness costs may have both short- and long-term consequences for the evolution of populations in response to a warming world.